UJI EFEK ANTIUDEMA SEDIAAN SALEP EKSTRAK DAUN SURUHAN (Peperomia pellucida L ) SECARA TOPIKAL PADA KULIT PUNGGUNG MENCIT (Mus musculus) - Ananda Ramadani (Jurnal Kesehatan Yamasi Makassar, 2022)
The aim of this study was to determine the anti-udema effect of suruhan leaf extract ointment (Peperomia pellucida) topically on the back skin of mice (Mus musculus). The research method used was a laboratory experimental study, to determine the anti-udema effect of the ointment of suruhan leaf extract (Peperomia pellucida) on the back skin of mice (Mus musculus) which was carried out at the Pharmacology Laboratory of the Yamasi Pharmacy Academy Makassar. Suruhan leaves (Peperomia pellucida L) were extracted by maceration method using 96% ethanol as solvent. The extract obtained was then made into an ointment with concentrations of (F1) as an ointment base, (F2), 15% w/w and (F3) 25% w/w .The results of the study stated that the leaf extract of suruhan leaf extract (Peperomia pellucida L) was more effective as an anti-udema on the back skin of mice.